Manipulation and expression of recombinant DNA : a laboratory manual - Robertson, Dominique, 1951- (Academic Press, 1997)
This laboratory manual is designed for use in introductory biotechnology courses. Experiments are constructed in a modular fashion, lending this book both to the traditional semester course and the shorter intensive course. Its main objective is to expose students to the basic research protocols used in molecular biology and biochemistry labs. This text covers techniques in detail and teaches students to culture and transform bacteria, grow vector plasmids, purify insert DNA, ligate vector and insert, and ultimately express protein and assay its activity. Comprehensive and complete, this text examines the underlying techniques used in all basic research and biotechnology laboratories